نظرية (المعرفة، والتعارف، والاعتراف) عند الشيخ علي يحي معمر - تفوشيت, خالد (Sharwes Scientific Journal, 2023)
Hospital-associated infections have led to a significant increment of morbidity and mortality among patients. Ultraviolet irradiation C (UVC) has emerged as an effective strategy for microbial control in hospitals and indoor public spaces. This review article highlights the current information regarding UV-C and Far-UV Technology disinfection capabilities and applications. UVC is commonly applied for air, surface, and water disinfection. UV irradiation (100 to 400 nm) is fractionated into four main regions by their wavelength and energy: Far-UV from 200 to 235 nm, short wave ultraviolet (UV-C) from 200 to 280 nm, UV-medium wave (UV-B) from 280 to 315 nm, and UV long wave (UV-A) from 315 to 400 nm. UV-C devices such as, Robots, Mercury-vapor lamps and diodes(UVC-LEDs) has the ability to disinfect airports and transport stations. However, overexposure to UV-C radiation can cause erythema, or sunburn like lesions on the skin, and photo keratitis in the eyes. Hence, for the application of UV-C light, safety is one of the primary considerations. Published studies on the effectiveness of UV-C radiation on surfaces and the surrounding environment showed that for bacterial inactivation it was more than 99.9% within 15 minutes, and the reduction in C. difficile spores was 99.8% within 50 minutes. A recent study showed 87.4 %, 99.9 % and a total inactivation of SARS-CoV-2 after 1, 10 and 20 s of treatment by UVC-LED (280 nm; 37.5 mJ/cm2), respectively. In rooms occupied by patients with MRSA, UV-C irradiation of approximately 15 minutes duration resulted in a decrease in total CFUs per plate (mean, 384 CFUs vs 19 CFUs; P < .001), in the number of samples positive for MRSA (81 [20.3%] of 400 plates vs 2 [0.5%] of 400 plates; P < .001), and in MRSA counts per MRSA-positive plate (mean, 37 CFUs vs 2 CFUs; P < .001). Far-UV-C(222nm) can eliminate pathogens including COVID-19 and other viral diseases without causing any health risks in spaces with simultaneous human presence. The Far-UV-based devices/lights can be administered to be used as an adjunctive procedure to the standard chemical methods in public indoor spaces such as hospitals, health clinics, schools, sport centers and public transport to minimize the risk of pathogens contamination and propagation, saving costs by reducing manual cleaning and equipment maintenance provided by manpower.